fMRI Adaptation between Action Observation and Action Execution Reveals Cortical Areas with Mirror Neuron Properties in Human BA 44/45 - de la Rosa, Stephan; Schillinger, Frieder L.; Bülthoff, Heinrich H.; Schultz, Johannes; Uludag, Kamil (Frontiers in Human Neuroscience, 2016)
Mirror Neurons (MNs) are considered to be the supporting neural mechanism for action understanding. MNs have been identified in monkey’s area F5. The identification of MNs in the human homologue of monkeys’ area F5 (BA 44/45) has been proven methodologically difficult. Cross-modal fMRI adaptation studies supporting the existence of MNs restricted their analysis to a-priori candidate regions, whereas studies that failed to find evidence used non-object-directed actions. We tackled these limitations by using object-directed actions differing only in terms of their object directedness in combination with a cross-modal adaptation paradigm and a whole-brain analysis. Additionally, we tested voxels’ BOLD response patterns for several properties previously reported as typical mirror neuron response properties. Our results revealed 52 voxels in left inferior frontal gyrus (particularly BA 44/45), which respond to both motor and visual stimulation and exhibit cross-modal adaptation between the execution and observation of the same action. These results demonstrate that part of human inferior frontal gyrus (IFG), specifically BA 44/45, has BOLD response characteristics very similar to monkey’s area F5.